Delivery of liothyronine by microneedle patch for the treatment of hypothyroidism - Yasmine Gomaa; Tasnuba Hasin; Martin N. Griffin; Thy C. Nguyen; Richard K. Noel; Laura O’Farrell; Elizabeth A. McAninch; Ann Marie Kaiser; Levi B. Wood; Mark R. Prausnitz (Drug Delivery and Translational Research, 2026)

Development of a microneedle patch for delivery of mRNA-lipid nanoparticles - Sophia H. Sakers; B. Pradeep K. Reddy; Gianna Fiduccia; Katherine E. Byrne; Ingrid Stén; Julie Kim; Afsane Radmand; James E. Dahlman; Mark R. Prausnitz (Drug Delivery and Translational Research, 2026)
mRNA delivered by microneedle patch (MNP) can enable painless delivery, reduced need for healthcare expertise, and improved thermostability. In this study, we investigated formulation and manufacturing approaches for developing MNPs that deliver mRNA-loaded lipid nanoparticles (LNPs) encoding luciferase as a reporter protein during MNP fabrication and storage, including mRNA-LNP concentration, formulation, pH, excipients, and backing material. MNPs were assessed for mRNA-LNP size, encapsulation efficiency, and protein expression in vitro and in vivo. MNPs fabricated with mRNA-LNPs initially prepared at a higher concentration yielded superior expression compared to mRNA-LNP concentration by centrifugation or tangential flow filtration. Acidic pH during MNP manufacturing enabled greater expression in vitro. However, no such correlation was observed in vivo. Polyvinyl alcohol (PVA) best stabilized mRNA-LNPs during the MNP manufacturing process amongst the tested polymers. Incorporating sugars in MNPs did not further improve stability. Low temperature drying (5 °C) preserved mRNA functionality better compared to drying at 25 °C and 40 °C. Though there was significant activity loss initially (87% loss in 2 days at 40 °C), mRNA expression was stabilized for extended subsequent periods even at accelerated conditions (10% additional loss after 28 days at 40 °C). Our systematic approach identified key parameters for successful formulation and manufacturing approaches to incorporate mRNA-LNPs into MNPs, which could expand access to mRNA-based medical interventions.

Rapid local anesthesia in children enhanced by STAR particles: a first-in-humans, randomized clinical trial - Andrew R. Tadros; Mark R. Prausnitz; Eric I. Felner (Drug Delivery and Translational Research, 2026)

Thermostability of tetanus toxoid vaccine encapsulated in metal-organic frameworks - Rohan Murty; Krista S. Walton; Mark R. Prausnitz (Drug Delivery and Translational Research, 2025)
Most vaccines require refrigerated transport and storage, which is costly, challenging in low-resource settings, and results in the loss of up to 50% of vaccines globally due to “cold-chain” failures. Here, tetanus toxoid vaccine (TT) was thermostabilized by encapsulation within a metal-organic framework (MOF), zeolitic imidazolate framework-8 (TT@ZIF-8). Its physicochemical properties were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, and confocal microscopy. Unencapsulated TT fell below the 80% activity threshold within 4 days at 40˚C and 60˚C according to immunoassay analysis. Aqueous suspensions of TT@ZIF-8 also declined below 80% activity within a week at both temperatures, likely due to MOF degradation in water. Dried TT@ZIF-8 performed better, retaining 80% stability for 33 days at 40˚C and 22 days at 60˚C. When TT@ZIF-8 was suspended in a non-aqueous mixture of propylene glycol and ethanol, it remained 80% stable for approximately 4 months at 40˚C and 2.5 months at 60˚C. Arrhenius modeling predicted this formulation may qualify for “controlled temperature chain” designation, allowing partial vaccine removal from the cold chain. These studies suggest that MOF encapsulation of vaccines like TT can enable dramatic improvements in vaccine stability during storage without refrigeration. Graphical abstract

Multi-Layered Microneedles Loaded with Microspheres - Andrew R. Tadros; Xin Dong Guo; Mark R. Prausnitz (AAPS PharmSciTech, 2025)

The promise of microneedle technologies for drug delivery - Ryan F. Donnelly; Mark R. Prausnitz (Drug Delivery and Translational Research, 2024)

Role of drug delivery technologies in the success of COVID-19 vaccines: a perspective - Hagar I. Labouta; Robert Langer; Pieter R. Cullis; Olivia M. Merkel; Mark R. Prausnitz; Yasmine Gomaa; Sara S. Nogueira; Tushar Kumeria (Drug Delivery and Translational Research, 2022)

Fabrication of pure-drug microneedles for delivery of montelukast sodium - Erkan Azizoglu; Ozgen Ozer; Mark R. Prausnitz (Drug Delivery and Translational Research, 2022)

Fabrication of microneedle patches with lyophilized influenza vaccine suspended in organic solvent - Yoo Chun Kim; Jeong Woo Lee; E. Stein Esser; Haripriya Kalluri; Jessica C. Joyce; Richard W. Compans; Ioanna Skountzou; Mark R. Prausnitz (Drug Delivery and Translational Research, 2021)

Development of a thermostable microneedle patch for polio vaccination - Chandana Kolluru; Yasmine Gomaa; Mark R. Prausnitz (Drug Delivery and Translational Research, 2019)

Challenges and Future Prospects for the Delivery of Biologics: Oral Mucosal, Pulmonary, and Transdermal Routes - Javier O. Morales; Kristin R. Fathe; Ashlee Brunaugh; Silvia Ferrati; Song Li; Miguel Montenegro-Nicolini; Zeynab Mousavikhamene; Jason T. McConville; Mark R. Prausnitz; Hugh D. C. Smyth (The AAPS Journal, 2017)

Long-term stability of influenza vaccine in a dissolving microneedle patch - Matthew J. Mistilis; Jessica C. Joyce; E. Stein Esser; Ioanna Skountzou; Richard W. Compans; Andreas S. Bommarius; Mark R. Prausnitz (Drug Delivery and Translational Research, 2017)

Enhanced Stability of Inactivated Influenza Vaccine Encapsulated in Dissolving Microneedle Patches - Leonard Y. Chu; Ling Ye; Ke Dong; Richard W. Compans; Chinglai Yang; Mark R. Prausnitz (Pharmaceutical Research, 2016)

Improved immunogenicity of individual influenza vaccine components delivered with a novel dissolving microneedle patch stable at room temperature - Elena V. Vassilieva; Haripriya Kalluri; Devin McAllister; Misha T. Taherbhai; E. Stein Esser; Winston P. Pewin; Joanna A. Pulit-Penaloza; Mark R. Prausnitz; Richard W. Compans; Ioanna Skountzou (Drug Delivery and Translational Research, 2015)

Reliability and accuracy of intradermal injection by Mantoux technique, hypodermic needle adapter, and hollow microneedle in pigs - James J. Norman; Jyoti Gupta; Samirkumar R. Patel; Sara Park; Courtney Jarrahian; Darin Zehrung; Mark R. Prausnitz (Drug Delivery and Translational Research, 2014)

Transdermal Delivery of Molecules is Limited by Full Epidermis, Not Just Stratum Corneum - Samantha N. Andrews; Eunhye Jeong; Mark R. Prausnitz (Pharmaceutical Research, 2013)

Microchip for Sustained Drug Delivery by Diffusion Through Microchannels - Seung Ho Lee; Min Park; Chun Gwon Park; Ji Eun Lee; Mark R. Prausnitz; Young Bin Choy (AAPS PharmSciTech, 2012)

Transdermal Insulin Delivery Using Microdermabrasion - Samantha Andrews; Jeong Woo Lee; Seong-O Choi; Mark R. Prausnitz (Pharmaceutical Research, 2011)

The Rule of Five for Non-Oral Routes of Drug Delivery: Ophthalmic, Inhalation and Transdermal - Young Bin Choy; Mark R. Prausnitz (Pharmaceutical Research, 2011)

Suprachoroidal Drug Delivery to the Back of the Eye Using Hollow Microneedles - Samirkumar R. Patel; Angela S. P. Lin; Henry F. Edelhauser; Mark R. Prausnitz (Pharmaceutical Research, 2011)

Stability Kinetics of Influenza Vaccine Coated onto Microneedles During Drying and Storage - Yeu-Chun Kim; Fu-Shi Quan; Richard W. Compans; Sang-Moo Kang; Mark R. Prausnitz (Pharmaceutical Research, 2011)

Ultrasound-Enhanced Drug Transport and Distribution in the Brain - Ying Liu; Sumit Paliwal; Krystof S. Bankiewicz; John R. Bringas; Gill Heart; Samir Mitragotri; Mark R. Prausnitz (AAPS PharmSciTech, 2010)

Formulation of Microneedles Coated with Influenza Virus-like Particle Vaccine - Yeu-Chun Kim; Fu-Shi Quan; Richard W. Compans; Sang-Moo Kang; Mark R. Prausnitz (AAPS PharmSciTech, 2010)

Intrascleral Drug Delivery to the Eye Using Hollow Microneedles - Jason Jiang; Jason S. Moore; Henry F. Edelhauser; Mark R. Prausnitz (Pharmaceutical Research, 2009)

Flux Across Microneedle-treated Skin is Increased by Increasing Charge of Naltrexone and Naltrexol In Vitro - Stan L. Banks; Raghotham R. Pinninti; Harvinder S. Gill; Peter A. Crooks; Mark R. Prausnitz; Audra L. Stinchcomb (Pharmaceutical Research, 2008)

Flux Across of Microneedle-treated Skin is Increased by Increasing Charge of Naltrexone and Naltrexol In Vitro - Stan L. Banks; Raghotham R. Pinninti; Harvinder S. Gill; Peter A. Crooks; Mark R. Prausnitz; Audra L. Stinchcomb (Pharmaceutical Research, 2008)

Coating Formulations for Microneedles - Harvinder S. Gill; Mark R. Prausnitz (Pharmaceutical Research, 2007)

Polymer Microneedles for Controlled-Release Drug Delivery - Jung-Hwan Park; Mark G. Allen; Mark R. Prausnitz (Pharmaceutical Research, 2006)

Microinfusion Using Hollow Microneedles - Wijaya Martanto; Jason S. Moore; Osama Kashlan; Rachna Kamath; Ping M. Wang; Jessica M. O'Neal; Mark R. Prausnitz (Pharmaceutical Research, 2006)

Transdermal Delivery of Insulin Using Microneedles in Vivo - Wijaya Martanto; Shawn P. Davis; Nicholas R. Holiday; Jenny Wang; Harvinder S. Gill; Mark R. Prausnitz (Pharmaceutical Research, 2004)

Intracellular Drug Delivery Using Low-Frequency Ultrasound: Quantification of Molecular Uptake and Cell Viability - Keyvan Keyhani; Héctor R Guzmán; Aimee Parsons; Thomas N. Lewis; Mark R. Prausnitz (Pharmaceutical Research, 2001)

Predicted Permeability of the Cornea to Topical Drugs - Aurélie Edwards; Mark R. Prausnitz (Pharmaceutical Research, 2001)

Magainin-Mediated Disruption of Stratum Corneum Lipid Vesicles - Shilpa Kaushik; Arthi Krishnan; Mark R. Prausnitz; Peter J. Ludovice (Pharmaceutical Research, 2001)

Non-Invasive Assessment and Control of Ultrasound-Mediated Membrane Permeabilization - Jin Liu; Thomas N. Lewis; Mark R. Prausnitz (Pharmaceutical Research, 1998)

Macromolecules as Novel Transdermal Transport Enhancers for Skin Electroporation - Rita Vanbever; Mark R. Prausnitz; Véronique Préat (Pharmaceutical Research, 1997)